2021
DOI: 10.1371/journal.pone.0258783
|View full text |Cite
|
Sign up to set email alerts
|

Using a new diagnostic tool to predict lymph node metastasis in advanced epithelial ovarian cancer leads to simple lymphadenectomy decision rules: A multicentre study from the FRANCOGYN group

Abstract: Objective The aim of this study was to develop a new diagnostic tool to predict lymph node metastasis (LNM) in patients with advanced epithelial ovarian cancer undergoing primary cytoreductive surgery. Materials and method The FRANCOGYN group’s multicenter retrospective ovarian cancer cohort furnished the patient population on which we developed a logistic regression model. The prediction model equation enabled us to create LNM risk groups with simple lymphadenectomy decision rules associated with a user-fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Many previous studies demonstrate that it was feasible to improve the diagnostic e ciency in LNM by clinical factors, radiological ndings, and radiomics features extracted from PET or CT images. A new diagnostic tool based on multivariate analysis including three variables: pelvic and/or para-aortic LNM on CT PET/CT, and initial PCI ≥ 10, initial CA125 ≥ 500 was proposed 27 . Another study used preoperative radiological scores to predict pelvic and/or para-aortic LNM 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies demonstrate that it was feasible to improve the diagnostic e ciency in LNM by clinical factors, radiological ndings, and radiomics features extracted from PET or CT images. A new diagnostic tool based on multivariate analysis including three variables: pelvic and/or para-aortic LNM on CT PET/CT, and initial PCI ≥ 10, initial CA125 ≥ 500 was proposed 27 . Another study used preoperative radiological scores to predict pelvic and/or para-aortic LNM 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the predictive value of PET metabolic parameters in AEOC 25,27,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer antigen-125 (CA125), a reliable biomarker, is widely used in ovarian cancer screening, diagnosis, and treatment monitoring [ 20 ]. CA125 was also identified as an independent predictor of LN involvement [ 21 , 22 ]. Moreover, the presence of bilateral tumours was suggestive of the presence of LNM [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no study to evaluate the correlation between PET/CT-related parameters and LNM, especially OLNM. Previous studies have demonstrated that hypermetabolic LN on PET/CT, initial CA125 ≥ 500, and initial peritoneal cancer index (PCI) ≥ 10 were independently and significantly associated with pelvic and/or para-aortic LNM 26 , 27 . Recently, many researchers have focused on radiomics features of PET/CT or contrast-enhanced CT in predicting LNM in AEOC, among which LNM assessment has been proven to have a certain significant improvement 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%